A Theory of Syllabification and Segmental Alternation : With Studies on the Phonology of French, German, Tonkawa and Yawelmani. - Noske, Roland (Linguistische Arbeiten., 1993)
Theory of Syllabification and Segmental Alternation: With Studies on the Phonology of French, German, Tonkawa and Yawelmani (Linguistische Arbeiten).